2018
DOI: 10.1136/bmjophth-2018-000204
|View full text |Cite
|
Sign up to set email alerts
|

Role of corneal biomechanical properties in predicting of speed of myopic progression in children wearing orthokeratology lenses or single-vision spectacles

Abstract: ObjectiveTo determine the characteristics of children who were likely to progress rapidly and gain the greatest benefit from orthokeratology (ortho-k) treatment.Methods and analysisThe files of 113 children who participated in two myopia control studies and wore either ortho-k lenses (n=62) or single-vision spectacles (SVS) (n=51) were reviewed. Baseline cycloplegic subjective refraction, central corneal thickness, axial length, keratometry, intraocular pressure, corneal biomechanical properties and 24-month a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 48 publications
3
16
2
Order By: Relevance
“…The biomechanical behavior of the cornea is affected by several factors such as age, IOP, CCT, corneal hydration status, corneal tissue composition, and several other factors, some of which are still under investigation (McMonnies, 2012 ; Roberts, 2014 ). The results of this study demonstrate a positive correlation between CCT, mean keratometry, and IOPnct with both CH and CRF, while AXL showed a negative correction only with CH, in keeping with previous studies (Wong and Lam, 2015 ; Qiu et al, 2016 ; Wan et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The biomechanical behavior of the cornea is affected by several factors such as age, IOP, CCT, corneal hydration status, corneal tissue composition, and several other factors, some of which are still under investigation (McMonnies, 2012 ; Roberts, 2014 ). The results of this study demonstrate a positive correlation between CCT, mean keratometry, and IOPnct with both CH and CRF, while AXL showed a negative correction only with CH, in keeping with previous studies (Wong and Lam, 2015 ; Qiu et al, 2016 ; Wan et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…Whilst a previous study suggested that CH as corneal biomechanical parameter can predict myopia progression in children (Wan et al, 2018); the results of the current study suggest that although there are no significant differences in CH in different myopia groups, there is a positive correlation between CH with SE overall. However, the present patient cohort only included adults and the results cannot be extrapolated to children.…”
Section: Discussioncontrasting
confidence: 84%
“…This study proves that the initial corneal thickness has no correlation with the axial elongation, which is consistent with the conclusions of the current literature [12,27]. Lee et al concluded that the initial corneal thickness was negatively correlated with the axial elongation, but they proposed that this correlation is highly dependent on the age, and believed that the younger wearers had thinner and more exible corneal thickness which is less likely to be affected by the cornea shape changes caused by the orthokeratology lens [11].…”
Section: Discussionsupporting
confidence: 93%
“…While the geometric properties of the cornea change following ortho-k, the magnitude of change does not correlate with metrics of corneal biomechanics. A recent study [125] reported a significant difference in corneal hysteresis in spectacle-wearing children showing slow and fast axial elongation and hence, it may be beneficial to recommend ortho-k as early as possible for myopic children with low corneal hysteresis.…”
Section: Corneal Biomechanicsmentioning
confidence: 99%